2021
DOI: 10.1007/s00296-021-04794-7
|View full text |Cite
|
Sign up to set email alerts
|

Can the SARS-CoV-2 infection trigger systemic lupus erythematosus? A case-based review

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune and multisystemic chronic inflammatory disease that can affect various organs, including skin, joints, kidneys, lungs and the nervous system. Infectious agents have long been implicated in the pathogenesis of SLE. The new viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown that, in genetically predisposed patients could trigger the presentation or exacerbation of the autoimmune disease. We herein report a case of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
95
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 38 publications
0
95
0
4
Order By: Relevance
“…A male patient with lupus presenting with arthritis and thrombocytopenia developed Coombs' positive haemolytic anaemia along with APLA positivity [81]. A review has found two novel cases of lupus, along with flares in ACPA anti-citrullinated peptide antibody, ANA antinuclear antibodies, HLA human leukocyte antigen, IAS intra-articular steroids, NSAID non-steroidal anti-inflammatory drugs, RF rheumatoid factor [71]. A large multi-centric cohort has shown that patients with autoimmune diseases may be at higher risks for developing COVID-19 than the general population [82].…”
Section: Covid-19 In Patients With Various Autoinflammatory and Autoimentioning
confidence: 99%
“…A male patient with lupus presenting with arthritis and thrombocytopenia developed Coombs' positive haemolytic anaemia along with APLA positivity [81]. A review has found two novel cases of lupus, along with flares in ACPA anti-citrullinated peptide antibody, ANA antinuclear antibodies, HLA human leukocyte antigen, IAS intra-articular steroids, NSAID non-steroidal anti-inflammatory drugs, RF rheumatoid factor [71]. A large multi-centric cohort has shown that patients with autoimmune diseases may be at higher risks for developing COVID-19 than the general population [82].…”
Section: Covid-19 In Patients With Various Autoinflammatory and Autoimentioning
confidence: 99%
“…1 The new viral infection caused by SARS-CoV-2 seems to lead to the onset or exacerbation of autoimmune diseases in genetically predisposed patients. [2][3][4] SLE is an autoimmune disease prone to flare-ups that are linked to significant morbimortality. Immunosuppressionrelated infections are one of the leading causes of premature death in patients with SLE.…”
mentioning
confidence: 99%
“…However, there are currently no data to support a higher infection rate or an increased risk for fatal outcome related to COVID-19 in these patients. [2][3][4][5] One could even speculate the SLE treatment can protect against the serious complications related to COVID-19. 2 In this regard, we read the relevant paper by Mathian et al 1 who evaluated the clinical course of COVID-19 in patients with SLE treated with hydroxychloroquine.…”
mentioning
confidence: 99%
“…We recently read with interest the article entitled "Can the SARS-CoV-2 infection trigger systemic lupus erythematosus? A case-based review" by Gracia-Ramos et al [1]. The authors reviewed emerging cases of SARS-CoV-2 infection either flaring-up previously diagnosed-SLE or triggering de novo SLE, and briefly pondered on the underlying mechanistic pathways leading to this association [1].…”
mentioning
confidence: 99%
“…A case-based review" by Gracia-Ramos et al [1]. The authors reviewed emerging cases of SARS-CoV-2 infection either flaring-up previously diagnosed-SLE or triggering de novo SLE, and briefly pondered on the underlying mechanistic pathways leading to this association [1]. Here, we would like to highlight the plasmacytoid dendritic cell (pDC) and its major product, type I interferons (IFNs), as a possible link that may explain SLE development or flare-up during the course of SARS-Cov-2 infection.…”
mentioning
confidence: 99%